2021
DOI: 10.3389/fneur.2021.700485
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of Sporadic Creutzfeldt–Jakob Disease: A Retrospective Study in Eastern China

Abstract: Objective: We aimed to characterize the epidemiological and clinical characteristics of sporadic Creutzfeldt–Jakob disease (sCJD) in eastern China in this retrospective study.Methods: This study enrolled 67 patients with sCJD hospitalized in a grade-A tertiary hospital in eastern China from January 2010 to January 2020. Demographic data, clinical symptoms, brain magnetic resonance imaging (MRI), electroencephalogram (EEG), cerebrospinal fluid (CSF) 14-3-3 protein test, polymerase chain reaction (PCR), and DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(112 reference statements)
1
7
0
Order By: Relevance
“…Ancillary tests can help clinicians differentiate CJD from other neurological diseases and ophthalmic disorders. Brian MRI is an essential tool in the diagnosis of CJD, and our study showed that the sensitivity of MRI was superior to those of CSF 14-3-3 and EEG, which is consistent with previous studies [ 23 , 24 , 25 , 26 ]. In our study, the median time from the disease’s onset to the presence of typical neuroimaging manifestations of CJD was 2 months.…”
Section: Discussionsupporting
confidence: 92%
“…Ancillary tests can help clinicians differentiate CJD from other neurological diseases and ophthalmic disorders. Brian MRI is an essential tool in the diagnosis of CJD, and our study showed that the sensitivity of MRI was superior to those of CSF 14-3-3 and EEG, which is consistent with previous studies [ 23 , 24 , 25 , 26 ]. In our study, the median time from the disease’s onset to the presence of typical neuroimaging manifestations of CJD was 2 months.…”
Section: Discussionsupporting
confidence: 92%
“…Despite its rarity, CJD poses a significant Biomarkers such as increased amounts of 14-3-3 and Tau proteins in CSF have also been associated to CJD. 11 Furthermore, genetic testing on variations of the PRNP gene have been identified as potential indicators for prion diseases. For example, research on human prion diseases focused on the PRNP gene and its variations at codon 129 have emphasized its influence on vulnerability, medical progression and molecular subtypes of sporadic CJD in East and South Asian communities.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has a distinctive clinical presentation, which includes rapidly developing dementia, coupled with additional neurological symptoms such as ataxia, myoclonus and visual abnormalities. 9 11 Electroencephalogram (EEG) and magnetic resonance imaging (MRI) are essential diagnostic tools, and the detection of 14-3-3 protein in the cerebrospinal fluid (CSF) can confirm the diagnosis. While CJD is rare, it has significant implications for public health due to its high mortality rate and the potential for iatrogenic spread.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the fact that 98.5% of sCJD patients have the MM genotype at locus 129, which also implies a lack of MV1, MV2, VV1, and VV2 type sCJD cases in China, which constitute approximately 40–55% of the sCJD cases in the Caucasian population 4–7,9 . Furthermore, the overall survival of Chinese sCJD patients is comparable to or longer than that of Caucasian patients 24–27 . Since MM1‐type sCJD is associated with significantly shorter survival compared to other forms of sCJD, the predominance of MM2‐type sCJD with a median survival of 12–36 months may contribute to the comparable or longer survival of Chinese sCJD patients.…”
Section: Discussionmentioning
confidence: 99%